TOPOGRAPHIC CHANGES OF THE MACULA AFTER CLOSURE OF IDIOPATHIC MACULAR HOLE. Issue 4 (April 2017) - Pak, Kang Yeun; Park, Keun Heung; Kim, Kyong Ho; Park, Sung Who; Byon, Ik Soo; Kim, Hyun Woong; Chung, In Young; Lee, Joo Eun; Lee, Sang Joon; Lee, Ji Eun
Abstract : Purpose: To investigate retinal displacement in the macula after surgical closure of idiopathic macular hole and to identify factors correlated with displacement. Methods: This retrospective multicenter study included 73 eyes of 73 patients having idiopathic macular hole. A custom program was developed to compare the position of the retinal vessels in the macula between preoperative and postoperative photographs. En face images of a 6 mm × 6 mm optical coherence tomography volume scans were registered to calculate the scale. A grid comprising 16 sectors in 2 rings (inner; 2–4 mm and outer; 4–6 mm) was superimposed. The displacement of the retinal vessels was measured as a vector value by comparing the location of the retinal vessels in each sector. The correlation between displacement and various clinical parameters was analyzed. Results: The average displacement was 57.2 μ m at an angle of −3.3° (nasal and slightly inferior). Displacement was larger in the inner ring (79.2 μ m) than in the outer ring (35.3 μ m, P < 0.001), and larger in the temporal sectors than in the corresponding nasal sectors ( P ⩽ 0.008). Inferior and superior displacement was noted in the superior and inferior sectors, respectively. Multiple regression analysis revealed that basal horizontal macular hole diameter and size of internal limiting membrane removal were independent factors of displacement. Conclusion: The macula was displaced centripetally, nasally, and slightly inferiorly after surgical closure of idiopathic macular hole. Hole closure, contraction of the nerve fiber layer, and gravity are the suggested mechanisms of macular displacement caused by internal limiting membrane peeling. Abstract : Supplemental Digital Content is Available in the Text.Displacement map of the retinal vessels demonstrated that they were displaced centripetally, nasally, and slightly inferiorly after surgical closure of macular hole suggesting hole closure, nerve fiber layer contraction, and gravity as the mechanisms.